Marco Sassòli, International Humanitarian Law: Rules, Controversies, and Solutions to Problems Arising in Warfare, Edward Elgar Publishing, Cheltenham: 2019, pp. 720 (Polish Yearbook of International Law, 2021)
International Humanitarian Law. Rules, Controversies, and Solutions to Problems Arising in Warfare confirm sassòli’s position as an expert in the role of IHL, and specialists in other branches of international law should also take notice of this fascinating (how rarely can we can use this expression in reference to a handbook!) publication. The result is splendid. a giant, on whose arms other IHL researchers can grow, has spoken. it is well worthwhile to listen to him.